Analysis of risk factors and outcome in peritoneal dialysis patients with early-onset peritonitis: a multicentre, retrospective cohort study. Issue 2 (13th February 2020) - Ma, Xiaoyan; Shi, Yingfeng; Tao, Min; Jiang, Xiaolu; Wang, Yi; Zang, Xiujuan; Fang, Lu; Jiang, Wei; Du, Lin; Jin, Dewei; Zhuang, Shougang; Liu, Na
Abstract : Objectives: To investigate the risk factors associated with early-onset peritonitis (EOP) and their influence on patients' technique survival and mortality. Study design: Retrospective, cohort study. Setting: Three peritoneal dialysis (PD) units in Shanghai. Participants: PD patients from 1 June 2006 to 1 May 2018 were recruited and followed up until 31 December 2018. According to time-to-first episode of peritonitis, patients were divided into non-peritonitis (n=144), EOP (≤6 months, n=74) and late-onset peritonitis (LOP) (>6 months, n=139). Primary and secondary outcome measures: EOP was defined as the first episode of peritonitis occurring within 6 months after the initiation of PD. The outcomes were all-cause mortality and technique failure. Results: Of the 357 patients, 74 (20.7%) patients developed their first episode of peritonitis within the first 6 months. Compared with the LOP group, the EOP group had older ages, more female patients, higher Charlson Comorbidity Index (CCI) score, lower serum albumin levels and renal function at the time of initiation of PD, and higher diabetes mellitus and peritonitis rates (p<0.05). Staphylococcus was the most common Gram-positive organism in both EOP and LOP groups. The multivariate logistic regression analysis showed that factors associated with EOP included a higher CCI score (OR 1.285, p=0.011), lower serum albumin level (OR 0.924, p=0.016) and lower Kt/V (OR 0.600, p=0.018) at start of PD. In the Cox proportional-hazards model, EOP was more likely a predictor of technique failure (HR 1.801, p=0.051). There was no difference between EOP and LOP for all-cause mortality. Conclusion: A higher CCI score and lower serum albumin level and Kt/V at PD initiation were significantly associated with EOP. EOP also predicted a high peritonitis rate and poor clinical outcome.